Association between levels of serum ferritin and bone mineral density in Korean premenopausal and postmenopausal women: KNHANES 2008-2010. - Seung Joo Chon; Yun Rak Choi; Yun Ho Roh; Bo Hyon Yun; SiHyun Cho; Young Sik Choi; Byung Seok Lee; Seok Kyo Seo (PLoS ONE, 2014)
Background As women go through menopause, serum estrogen decreases and ferritin increases. Decreased serum estrogen is well known to cause detrimental effects on bone health; however, data on the associations of serum ferritin with BMD before and after menopause are still lacking. Therefore, this study aimed to investigate the association between serum ferritin levels and BMD in premenopausal and postmenopausal Korean women. Methods This study was performed using data from the 2008-2010 Korean National Health and Nutrition Examination Survey, including 7300 women (4229 premenopausal and 3071 postmenopausal). BMD was measured using dual X-ray absorptiometry at the femur and the lumbar spine, and serum ferritin levels were measured by chemiluminescent immunoassay. Results Median serum ferritin levels in postmenopausal women were higher than those in premenopausal women despite the same age ranges. Serum ferritin levels were only significantly correlated with BMD on the lumbar spine (β = -0.189, p-value = 0.005) in premenopausal women after adjusting confounding factors. Additionally, BMD on the lumbar spine had tended to decrease as serum ferritin quartiles increase (P for trend = 0.035) in premenopausal women after adjusting confounding factors. On the other hand, there were no significant associations between serum ferritin levels and BMD on the total femur and, femur neck in premenopausal women, and BMD on the total femur, femur neck, and lumbar spine in postmenopausal women. Conclusion Increased serum ferritin levels were significantly associated with BMD in premenopausal women, particularly on the lumbar spine, but not in postmenopausal women.